Analisa Pengaruh Produk, Kualitas Pelayanan, Harga, Dan Store Atmosphere Terhadap Minat Beli Di Dream Of Khayangan Art Resto Surabaya - Budi Utomo Sugiarto (Jurnal Strategi Pemasaran, 2014)
The rapid economic development of Indonesia looks of many emerging business ventures , one of which is a culinary efforts pretty much in demand. Surabaya including cities with high growth in the culinary business. Many businesses and restaurants where to eat cause tighter competition. Consumers are also increasingly critical in determining the choice of a restaurant that buying interest is not only based on product, service quality, and price. Dream of Khayangan Art Resto Surabaya as one of the restaurants in Surabaya are able to compete and survive , implementing a strategy not only to maintain the product, quality of service, price, but also store atmosphere.This study aims to analyze the influence of product, quality of service, price, and store atmosphere on buying interest Khayangan Dream of Art Resto Surabaya. This study will be carried out by distributing questionnaires to 100 respondents consumers Dream of Khayangan Art Resto Surabaya. The analysis technique used is quantitative analysis with multiple linear regression method. The research proves that there is a significant effect of the product, quality of service, price, and store atmosphere on consumer buying interest in Dream of Khayangan Art Resto Surabaya.